Leveraging incentives to increase HIV testing uptake among men: qualitative insights from rural Uganda - Alex Ndyabakira; Monica Getahun; Ambrose Byamukama; Devy Emperador; Stella Kabageni; Kara Marson; Dalsone Kwarisiima; Gabriel Chamie; Harsha Thirumurthy; Diane Havlir; Moses R. Kamya; Carol S. Camlin (BMC, 2019)
Abstract Background Few studies have explored how economic incentives influence behavioral outcomes. This study aimed to identify pathways of action of an incentives-based intervention to increase men's participation in HIV testing. Methods The qualitative study was embedded in a randomized-controlled trial that compared effectiveness of gain-framed, loss-framed and lottery-based incentives to increase HIV testing among men. Following testing at a community health campaign, 60 in-depth interviews were conducted with men systematically sampled on the basis of age, incentive group, and campaign attendance. Data were coded deductively and inductively for thematic content analysis. Results Incentives addressed men's structural, interpersonal and individual-level barriers to testing: offered at convenient locations, incentives offset costs of testing, in lost wages, which are exacerbated when livelihoods required mobility. Interpersonal barriers included anticipated stigma/fear of disclosure, social obligations, and negative peer influences. Providing incentives in public settings provided "social proof" that prizes could be won, and facilitated social support and positive norms by promoting testing with trusted others. Incentives had little influence when men appraised prize values to be low, disbelieved they would win a prize, or were already intrinsically motivated to test. Yet, incentives provided a behavioral 'cue to action' for many men who perceived themselves to be susceptible to HIV and perceived HIV disease to be severe, acting as secondary motivator for testing that "sweetened the deal". Conclusion Incentives can be an important 'lever' to promote men's healthy behaviors in resource-poor settings. HIV testing in convenient, public settings, when paired with incentives, provides multiple pathways to stimulate men's testing uptake. Trial registration Registered with ClinicalTrials.gov on 08/10/2016, ID: NCT02890459. The first participant was enrolled on 11th April 2016.